2008
DOI: 10.1111/j.1467-8624.2008.01235.x
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Responses to Interparental Conflict: A Meta‐Analysis of Their Associations With Child Adjustment

Abstract: A meta-analysis examined the relations between children's adjustment and children's cognitive, affective, behavioral, and physiological responses to interparental conflict. Studies included children between 5 and 19 years of age. Moderate effect sizes were found for the associations between cognitions and internalizing and externalizing behavior problems and self-esteem problems, negative affect and behavioral responses and internalizing behavior problems, and behavioral responses and self-esteem problems. Sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
226
1
17

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(261 citation statements)
references
References 73 publications
11
226
1
17
Order By: Relevance
“…Lower SCLR served as protective factor in children from highconflict homes exposed to the couple conflict. Conclusion: The current study advances the body of knowledge in this field by identifying risk patterns for the development of attention problems in children in relation to marital conflict exposure.Keywords: marital conflict; electrodermal activity; physiological reactivity; attention problems; emotional security; sensitization hypothesis 3 INTERPARENTAL CONFLICT, SCLR, AND CHILD'S ATTENTION The role of skin conductance level reactivity in the impact of children's exposure to interparental conflict on their attention performance Exposure to destructive interparental conflict increases child's risk for psychological problems such as externalizing and internalizing symptoms, impairments in social relationships, and poor academic achievement (Cummings & Davies, 2010;Grych & Fincham, 1990;Rhoades, 2008). Due to its role as predictor of a wide array of future adjustment problems (Masten & Coatsworth, 1998), the latter has become the focus of increasing interest.…”
mentioning
confidence: 99%
“…Lower SCLR served as protective factor in children from highconflict homes exposed to the couple conflict. Conclusion: The current study advances the body of knowledge in this field by identifying risk patterns for the development of attention problems in children in relation to marital conflict exposure.Keywords: marital conflict; electrodermal activity; physiological reactivity; attention problems; emotional security; sensitization hypothesis 3 INTERPARENTAL CONFLICT, SCLR, AND CHILD'S ATTENTION The role of skin conductance level reactivity in the impact of children's exposure to interparental conflict on their attention performance Exposure to destructive interparental conflict increases child's risk for psychological problems such as externalizing and internalizing symptoms, impairments in social relationships, and poor academic achievement (Cummings & Davies, 2010;Grych & Fincham, 1990;Rhoades, 2008). Due to its role as predictor of a wide array of future adjustment problems (Masten & Coatsworth, 1998), the latter has become the focus of increasing interest.…”
mentioning
confidence: 99%
“…A investigação empírica tem demonstrado sistematicamente que o funcionamento familiar é uma variável robusta na compreensão da saúde física e mental das crianças 2,4,33 . Em decorrência da clareza teórica do constructo que avalia, da sua dimensão reduzida, do tempo necessário na sua aplicação, da sua estrutura psicométrica e da facilidade de cotar e interpretar os dados, a PAM-R surge como um instrumento que pode aumentar a eficácia da avaliação do impacto das dimensões familiares (neste caso a aliança parental) no funcionamento e desenvolvimento psicológico das crianças, em contextos de prestação de cuidados de saúde primários, independentemente da configuração estrutural da família 34 .…”
Section: Discussionunclassified
“…Ao longo das últimas décadas, a investigação tem consistentemente demonstrado uma relação direta entre a saúde psicológica e física das crianças e variáveis familiares, tais como a qualidade da relação conjugal e da relação pais-criança (parentalidade) e o funcionamento familiar [1][2][3][4] . Mais recentemente, a investigação tem também revelado que a aliança parental é uma variável que assume igualmente relevo empírico na compreensão do funcionamento psicológico das crianças 5,6 .…”
Section: Introductionunclassified
“…In a metaanalysis on youth outcomes associated with exposure to interparental conflict, [52] found that effect sizes were larger for internalizing than for externalizing problems. [53] indicate that young adults' retrospective reports of perceived exposure to conflict between parents was associated with low levels of present psychological adjustment, including increased depression and anxiety symptoms and loss of emotional or behavioral control.…”
Section: Consequences Of Parental and Sibling Conflictmentioning
confidence: 99%